2005
DOI: 10.1002/jbm.a.30513
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of amino group density on surfaces of titanium dioxide nanoparticles covalently bonded to a silicone substrate for antibacterial and cell adhesion activities

Abstract: A composite consisting of titanium dioxide (TiO2) particle, the surface of which was modified with amino groups, and a silicone substrate through covalent bonding at their interface was developed, and antibacterial and cell adhesion activities of the composite were evaluated. The density of the amino groups on the TiO2 particle surface was controlled by the reaction time of the modification reaction. The degradation rate of CH3CHO in the presence of the TiO2 particles under UV irradiation decreased with an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Because systemic antibiotics often do not provide effective treatment for implant infections due to the phenomenon of drug resistance, it is important that the coating of the implant exhibit local antibacterial activity. In order to reduce the incidence of implant-associated infections, several biomaterial surface treatments have been proposed [18][19][20][21][22][23][24][25][26][27][28][29][30]. In particular, silver has raised the interest of many investigators because of its good antimicrobial action and low toxicity [30,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because systemic antibiotics often do not provide effective treatment for implant infections due to the phenomenon of drug resistance, it is important that the coating of the implant exhibit local antibacterial activity. In order to reduce the incidence of implant-associated infections, several biomaterial surface treatments have been proposed [18][19][20][21][22][23][24][25][26][27][28][29][30]. In particular, silver has raised the interest of many investigators because of its good antimicrobial action and low toxicity [30,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Several biomaterial surface treatments have been proposed as a means of reducing the incidence of implant-associated infections. There has been investigation into the covalent attachment of polycationic groups [18,19]; ion implantation, such as F+ [20]; impregnating or loading chitosan nanoparticles with antimicrobial agents [21,22]; coating implant surfaces with polymers drug-loaded [23,24]; and coating implant surfaces with either quaternary ammonium compounds, human serum albumin, or silver ions [25][26][27][28][29][30]. However, there are several shortcomings of these proposed techniques including limited chemical stability, local inflammatory reactions due to material composition, and a lack of controlled release kinetics from the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[11a, 74a] The grafting-from copolymerization technique is used more often than its counterpart,m ainly due to the highere fficiency and selectivity of the reaction between smaller, less sterically hinderedm onomers (see Scheme 9). For example, Okada et al [76] developed PDMS co-polymerized with acrylic acid by using ag rafting-from method and later TiO 2 modification.I ti s also used for the modificationo fs ilica particles that are later suspended in silicone. Poly(vinylbenzyltributylphosphonium chloride)( 24) [77] or polyurethanea re used as copolymers.…”
Section: Copolymerizationmentioning
confidence: 99%
“…Thus far, various nanoparticle-hydrogel composite systems comprising metallic nanoparticles, carbon nanotubes, clays, ceramics, magnetic nanoparticles, hydroxyapatite, or semiconducting nanoparticles have been reported. [26][27][28][29][30] One of the advantages of hydrogel encapsulation of nanoparticles is enhanced biocompatibility achieved through the presence of a hydrogel matrix between sensitive tissues and potentially harmful nanoparticles. For example, a recent study by Meenach et al 22 demonstrated more favorable cell viability for iron oxide nanoparticles encapsulated within poly-N-isopropylacrylamide hydrogel than for unencapsulated nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogel-coated magnetic iron oxide nanoparticles green light at 514 nm and a flux of 2.5 mW/cm 2 using an argon ion laser (Coherent Inc, Santa Clara, CA) at various exposure times (20,30, and 60 seconds) ( Figure 2B). In order to remove unreacted PEGDA, acryl-PEG-RGDS, and other unreacted components, coated MIONPs were washed using the Amicon Ultra centrifugal filter.…”
mentioning
confidence: 99%